Understanding mental health in developmental dyslexia through a neurodiversity lens: The mediating effect of school-connectedness on anxiety, depression and conduct problems. - Wilmot, Adrienne; Hasking, Penelope; Leitao, Suze; Hill, Elizabeth; Boyes, Mark (Wiley-Blackwell, 2024)
Dyslexia, a neurocognitive difference characterised by poor word-reading, is associated with elevated risk for internalising (e.g., anxiety) and externalising (e.g., aggression) mental health concerns, the reasons are largely unknown. We took a neurodiversity perspective and explored whether school-connectedness mediated these associations. A total of 283 primary school children (87 with dyslexia) and their caregivers (95.4% mothers) completed a battery of well-validated connectedness and mental health measures. Two mediation models (one for child-report and one for caregiver-report) tested direct and indirect effects of dyslexia on anxiety, depression and conduct problems via several domains of school-connectedness. After controlling for gender and neurodevelopmental conditions other than dyslexia, there were no direct effects of dyslexia on child- or caregiver-reported internalising symptoms or child-reported conduct problems. Dyslexia was associated with child and caregiver reported anxiety, depression and conduct problems via low levels of school (but not teacher, friend or peer) connectedness. Findings highlight school-connectedness as an important intervention target for the mental health of children with dyslexia. Future research is needed to test associations between dyslexia, school-connectedness and mental health over time.